The model of appearance and development of the rescue works safety has been worked out - Burminski Дмитрий Анатольевич; Modin Николай Константинович (Chrezvychaynye situatsii: obrazovanie i nauka, 2008)
The model is intended for calculation of the actual level of the rescue works safety. The calculation is based on the determination of the unfavorable events probabilities and guide forces at the all levels of the «tree unfavorable events».